Sleep deprivation affects tau phosphorylation in human cerebrospinal fluid - Barthélemy, Nicolas R. (Ann Neurol, 2020)
Tau hyperphosphorylation is an early step in tau-mediated neurodegeneration and is associated with intracellular aggregation of tau as neurofibrillary tangles, neuronal and synaptic loss, and eventual cognitive dysfunction in Alzheimer’s disease. Sleep loss increases the cerebrospinal fluid concentration of amyloid-β and tau. Using mass spectrometry, we measured tau and phosphorylated tau concentrations in serial samples of cerebrospinal fluid collected from participants who were sleep-deprived, treated with sodium oxybate, or allowed to sleep normally. We found that sleep loss affected phosphorylated tau differently depending on the modified site. These findings suggest a mechanism for sleep loss to increase risk of Alzheimer’s disease.